Low-heat high-strength cement-based material based on time-sharing regulation of hydration heat and preparation method thereof
Patent Information
- Application Number
- CN202611192133.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2046-08-07
AI Technical Summary
[0007]针对现有技术中水泥基材料水化热释放集中、温升峰值高以及传统低热化技术易导致强度损失和适应性不足的问题,本发明的目的在于提供一种基于分时调控水化热的低热高强水泥基材料及其制备方法,通过调控不同功能组分(成核惰性粉体与缓释激活颗粒)在水化过程中的响应时序,实现水化反应过程在时间维度上的重新分配,从而降低早龄期放热强度和温度峰值,并提高水泥基材料的力学性能
[0029](1)本发明通过构建成核惰性粉体与缓释激活颗粒协同调控体系,实现水泥水化过程在时间维度上的重新分配,使传统单峰集中放热模式向分布式放热模式转变,在保证材料强度发展的同时有效降低累计水化热量和温升峰值。
Smart Images

Figure CN122685387B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of cement-based materials technology, and more specifically, to a low-heat, high-strength cement-based material based on time-division controlled heat of hydration and its preparation method. Background Technology
[0002] Cement-based materials are widely used in engineering fields such as bridges, dams, nuclear power plant foundations, cast-in-place and prefabricated buildings due to their wide availability of raw materials, excellent mechanical properties, and strong adaptability to construction. Ordinary Portland cement releases a large amount of heat of hydration during the hydration process, especially at the early stages. For large-volume or highly confined structures, the internal heat is difficult to dissipate in time, easily leading to a large temperature difference between the inside and outside, which in turn generates temperature stress and induces temperature cracks, seriously affecting the durability and long-term service performance of the engineering structure.
[0003] To reduce the early-age temperature rise and heat release of cement-based materials, existing technologies mainly employ physical cooling methods, low-heat cementitious material substitution methods, and chemical admixture regulation methods. Physical cooling methods lower the system temperature through cooling water pipes, ice water, or liquid nitrogen, but these methods are complex to implement and costly. Low-heat cementitious material substitution methods (see patent application CN116282977A) partially replace cement with low-heat cement or mineral admixtures such as fly ash and slag powder, which can reduce heat release, but often result in decreased early strength and prolonged setting time. Chemical admixture regulation methods mainly suppress the hydration reaction rate through admixtures such as retarders and hydration heat inhibitors, thereby reducing the peak heat release, but generally suffer from poor system adaptability, dosage sensitivity, easy incompatibility reactions with cement components, and insufficient long-term stability.
[0004] Although existing patent applications with publication numbers CN104609767A and CN109293273A have proposed some hydration control schemes, they still mainly rely on complex admixture systems to achieve hydration inhibition, which has problems such as complex preparation processes, high economic costs, insufficient engineering adaptability, and performance stability that need to be improved.
[0005] More importantly, most existing technologies reduce the heat release of hydration by lowering the overall hydration rate. However, this still essentially represents a concentrated heat release mode and does not alter the temporal distribution characteristics of the cement hydration reaction. Therefore, it is difficult to fundamentally alleviate the temperature stress problem caused by concentrated heat release, and it is also difficult to achieve a balance between low-heat properties and mechanical properties.
[0006] Therefore, there is an urgent need to develop a scheme that can control the cement hydration process over time and release the heat of hydration in stages, and to obtain cement-based materials that balance low temperature rise and mechanical properties to meet the application needs of large-volume concrete, hydraulic structures, bridge engineering and other high-durability engineering structures. Summary of the Invention
[0007] To address the problems of concentrated heat release and high temperature peak in cement-based materials in existing technologies, as well as the tendency of traditional low-heat hydration techniques to lead to strength loss and insufficient adaptability, the present invention aims to provide a low-heat, high-strength cement-based material and its preparation method based on time-sequential control of heat of hydration. By controlling the response sequence of different functional components (nucleating inert powder and slow-release activating particles) during the hydration process, the hydration reaction process is redistributed over time, thereby reducing the early-age heat release intensity and temperature peak, and improving the mechanical properties of the cement-based material.
[0008] To achieve the above objectives, in a first aspect, the present invention provides a low-heat, high-strength cement-based material based on time-controlled hydration heat, comprising the following components by weight: 256-428 parts cement; 254-620 parts nucleating inert powder; 41-110 parts slow-release activating particles; 183-238 parts water; 1095-1429 parts river sand; and 1-2 parts water-reducing agent; wherein the nucleating inert powder provides nucleation sites during the early stages of cement hydration and has a particle size of less than 3 μm; the slow-release activating particles have a core-shell structure with a particle size of 3-15 μm, comprising an inner layer of mineral particles and an outer layer of silica sol coating with a thickness of 0.1-3 μm; the mineral particles include one or more of granulated blast furnace slag powder, fly ash, and metakaolin. It is understood that the present invention is not limited to these types of mineral particles, but can be any mineral particles that can react with Ca(OH)2 produced by cement hydration to produce secondary hydration product CSH gel, thereby reducing the internal porosity of cement-based materials and improving the compactness and later mechanical properties of the materials.
[0009] Nucleating inert powders do not chemically react with water and do not generate additional heat of hydration. They partially replace cement, reducing the amount of cement used per unit volume and thus decreasing the accumulated heat release in the early stages of hydration. Their ultrafine particles can fill the micropores between cement particles, increasing the density of the paste and thus improving the early mechanical properties of the material. Furthermore, nucleating inert powders exhibit significant heterogeneous nucleation and micro-filling effects; in the early stages of cement hydration, they can provide numerous heterogeneous nucleation sites for CSH gels, promoting the formation of hydration products and accelerating microstructure construction. The surface coating layer of the slow-release activating particles acts as a slow-release barrier layer, delaying the release of internal active components and thus mitigating the heat release from the calcium carbonate. 2+ SiO4 2-The dissolution rate of active ions is reduced, delaying the activation time of inner layer mineral particles in the hydration reaction. Finally, through specific particle size matching (the former <3 μm, the latter 3~15 μm) and activity sequence matching, low heat of hydration and high mechanical properties of cement-based materials are achieved throughout the hydration process by matching the nucleating inert powder and the slow-release activating particles.
[0010] Therefore, in the above technical solution, the synergistic effect of nucleating inert powder and slow-release activating particles enables different functional particles to participate in the hydration reaction at different ages. Among them, the nucleating inert powder promotes the generation of cement hydration products in the early age through the filling effect and heterogeneous nucleation effect, while the slow-release activating particles gradually release activity and continue to participate in the reaction in the later stage, reacting with Ca(OH)2 generated by cement hydration to produce secondary hydration product CSH gel. This achieves distributed control of the hydration heat release process in the time dimension, reduces the early age temperature rise peak, and promotes the coordinated development of the early and late mechanical properties of the material.
[0011] Furthermore, the cement is ordinary Portland cement. For example, the cement is ordinary Portland cement with a strength grade of 42.5, and its appropriate dosage can be obtained through a limited number of experiments based on the characteristics of the cement.
[0012] Furthermore, the early nucleation reinforcing powder is one or more of dolomite powder, limestone powder, basalt powder, and quartz powder. It is understood that this invention is not limited to these types of early nucleation reinforcing powders, but can also include inorganic inert powders that do not substantially participate in chemical reactions during cement hydration and do not generate additional heat of hydration.
[0013] Furthermore, the particle size of the slow-release activating particles is 5~15 μm. This further reduces the cumulative hydration heat and peak temperature rise during cement hydration, resulting in fewer microcracks and better durability in the obtained cement-based material.
[0014] Secondly, the present invention provides a method for preparing a low-heat, high-strength cement-based material, for preparing the low-heat, high-strength cement-based material as described above, comprising:
[0015] S1. Preparation of sustained-release activating particles: First, the mineral material is subjected to mechanical activation treatment by grinding, preferably using a ball mill or vibratory mill, with a grinding time of 1-4 hours; the specific surface area of the mechanically activated mineral particles is controlled at 450-900 m². 2 / kg; then the mechanically activated mineral particles are added to a silica sol dispersion for coating treatment, wherein the mass fraction of SiO2 in the silica sol is 10%~40%, the stirring speed is preferably 300~800 r / min, and the stirring time is preferably 30~120 min; finally, the mineral particles with a continuous silicon-oxygen network structure on the surface are heat-treated at 80~200 ℃ for 1~4 h to improve the structural stability of the silica sol coating layer; the particle size of the prepared slow-release activated particles is 3~15 μm, wherein the thickness of the silica sol coating layer is 0.1~3 μm;
[0016] S2. Weigh the water-reducing agent according to the ratio, mix it with water, and let it stand to obtain a mixed solution;
[0017] S3. The cement, nucleating inert powder with a particle size of less than 3 μm, and slow-release activating particles weighed according to the proportion are put into the mixer and stirred evenly to obtain a mixed powder.
[0018] S4. Add 2 / 3 of the volume of the mixed solution into the mixer and continue to stir until homogeneous to obtain a mixed slurry;
[0019] S5. The river sand weighed according to the proportion is added to the mixer and stirred. Then the remaining mixed solution is added and stirred to obtain a mixed slurry.
[0020] S6. The mixed slurry is injected into a mold for curing to form a solidified material; after curing, the material is demolded and cured for 1 to 28 days under the same curing environment to obtain a high-strength cement-based material.
[0021] In step S1 of the above technical solution, mechanical activation treatment can form micro-defect structures on the surface of mineral particles and increase the specific surface area, thereby increasing the number of active sites on the particle surface and improving the utilization efficiency of potential activity in the later stage. Simultaneously, it provides good interfacial bonding conditions for the formation of the subsequent coating layer. After coating treatment, a continuous silicon-oxygen network structure coating layer is formed on the surface of the mechanically activated mineral particles. Thermal stabilization treatment can promote further dehydration and polymerization of the coating layer, improve the structural stability of the coating layer, and form a surface regulation structure with slow-release characteristics. The slow-release activated particles are obtained through mechanical activation, surface coating, and thermal stabilization treatment. In the early stages, the coating layer acts as a barrier on the surface of mineral particles, inhibiting the rapid release of their internal active components, thereby reducing the hydration reaction rate and the degree of concentrated heat release, and reducing the peak temperature rise. In the middle and late stages, as the coating layer gradually undergoes hydration, dissolution, or structural damage, the internal active components of the mineral particles are gradually released and continue to participate in the hydration reaction. They react with Ca(OH)2 produced by cement hydration to form pozzolanic reaction, producing secondary hydration product CSH gel, which reduces the internal porosity of cement-based materials and improves the compactness and later mechanical properties of the materials.
[0022] The hydration process of the low-heat, high-strength cement-based material prepared using the above method is as follows: In the early stage, the nucleating inert powder provides nucleation sites, accelerating the hydration of the cement itself and compensating for the early strength loss caused by the reduction in cement content. Simultaneously, its physical dilution effect reduces the total heat of hydration. During this stage, the slow-release activating particles remain dormant and do not contribute to the heat of hydration. In the middle stage, when cement hydration slows down and the temperature rise becomes gradual, the coating layer of the slow-release activating particles begins to fail, and their internal active components are activated, subsequently generating secondary heat of hydration and forming CSH gel. This prolongs the total heat release time and reduces the peak value, while also filling the pores left by the early hydration, achieving continuous strength growth in the later stages. This dual-stage synergistic mode of rapid early nucleation and densification combined with delayed activation and filling enhancement in the middle stage is the core of achieving low-heat, high-performance cement-based materials.
[0023] Furthermore, before adding the remaining mixed solution, the mixer is operated at a low speed of 62±5 r / min. After adding the remaining mixed solution, the mixer is operated at a high speed of 125±10 r / min. This low-speed stirring ensures complete wetting of the cementitious material surface and the formation of a uniform collective rheological phase, while the strong shear stress field generated by high-speed stirring effectively breaks down the weak flocculation network and agglomerates between powder particles. This allows the additive molecules to obtain sufficient adsorption sites and fully distribute their dispersion efficiency, ultimately achieving a stable and uniform slurry distribution.
[0024] Furthermore, the maintenance is carried out in a maintenance environment with a temperature of 20±2℃ and a relative humidity of ≥95%.
[0025] It is understandable that the mineral material is dried before mechanical activation in the above preparation method to remove the surface moisture; the stirring and curing temperature can also be room temperature, and the stirring and curing time and other process parameters can be reasonably determined according to the uniformity or curing effect.
[0026] Furthermore, in steps S4 to S6, the peak temperature rise of the hydration reaction does not exceed 31.7 °C.
[0027] Finally, the present invention provides a low-heat, high-strength cementitious material prepared by the preparation method described above. Furthermore, the low-heat, high-strength cementitious material obtained after sufficient curing has a flexural strength of not less than 9.6 MPa and a compressive strength of not less than 57.9 MPa.
[0028] Compared with the prior art, the present invention has the following technical effects:
[0029] (1) This invention achieves the redistribution of cement hydration process in time dimension by constructing a synergistic regulation system of nucleated inert powder and slow-release activating particles, transforming the traditional single-peak concentrated heat release mode into a distributed heat release mode, effectively reducing the cumulative heat of hydration and the peak temperature rise while ensuring the development of material strength.
[0030] (2) The functional components used in this invention are all inorganic mineral materials, which have good compatibility with cement systems and can be applied to different types of cement-based materials. This avoids the problems of retarding failure, strength loss and insufficient long-term stability that are easily caused by traditional chemical admixtures such as retarders and heat of hydration inhibitors.
[0031] (3) This invention combines the heterogeneous nucleation effect of nucleating inert powder with the delayed reaction effect of slow-release activating particles to regulate the heat release law of hydration and promote the continuous generation of hydration products, thereby achieving a synergistic improvement in the low-heat performance and mechanical properties of the material.
[0032] (4) The raw materials used in this invention are widely available. Among them, the nucleating inert powder and the slow-release activating particles can be prepared from waste stone powder after stone processing and industrial by-product slag resources, which have good resource utilization value and environmental benefits. At the same time, the preparation process is simple and easy to implement in industrialization, and has good engineering application prospects. Attached Figure Description
[0033] The invention, its features and advantages will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings.
[0034] Figure 1 The cumulative exothermic curves are for Example 1 and Comparative Examples 1-3.
[0035] Figure 2 The exothermic rate curves are for Example 1 and Comparative Examples 1-3.
[0036] Figure 3 The cumulative exothermic curves are for Example 1 and Comparative Example 4.
[0037] Figure 4 The exothermic rate curves are for Example 1 and Comparative Example 4.
[0038] Figure 5 The cumulative exothermic curves are for Examples 1, 5, 5, and 6.
[0039] Figure 6 The heat release rate curves are for Examples 1, 5, 5, and 6. Detailed Implementation
[0040] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, but these are not intended to limit the scope of the invention.
[0041] All reagents used in the following examples or comparative examples are commercially available. The cement is ordinary silicate cement, branded as Southern Cement, grade PO 42.5. The nucleating inert powder is ultrafine dolomite powder with a particle size of less than 3 μm, sourced as a byproduct of processing and mining by Guizhou Wood Grain Stone Development Co., Ltd. It can also be replaced by one or more of limestone powder, basalt powder, and quartz powder with a particle size of less than 3 μm. The mineral material is blast furnace slag powder produced by Shanghai Esderui Building Materials Co., Ltd., and can also be replaced by one or more of fly ash and metakaolin. The water-reducing agent is PC-200 polycarboxylate high-performance water-reducing agent produced by Shanghai Yingshan New Material Technology Co., Ltd. Other silicate series cements, nucleating inert powders, mineral materials, or water-reducing agents used as substitutes have similar effects to those in the examples.
[0042] The testing methods used in the following examples or comparative examples are readily available prior art. The mechanical property testing of cement-based materials was performed in accordance with GB / T 17671-2021. The heat of hydration was tested using an eight-channel TAM adiabatic calorimeter to measure the cumulative heat release curve and heat release rate curve over 72 hours. The peak temperature rise was determined using the adiabatic temperature rise method, and engineering corrections were performed using a heat capacity correction model.
[0043] Example 1
[0044] This embodiment provides a low-heat, high-strength cement-based material and its preparation method, which includes the following steps:
[0045] S1. Preparation of slow-release activated particles: First, the blast furnace slag powder is mechanically activated by grinding using a ball mill or vibratory mill. The specific surface area of the mechanically activated blast furnace slag powder is controlled at 450~900 m². 2 / kg; then, the mechanically activated blast furnace slag powder is added to a silica sol dispersion and uniformly dispersed for coating treatment, so that the surface of the blast furnace slag powder is coated with a continuous silicon-oxygen network structure. The mass fraction of SiO2 in the silica sol is 10~40%; finally, the coated blast furnace slag powder is heat-treated at 80~200 ℃ for 1~4 h to improve the structural stability of the silica sol coating layer; the particle size of the prepared slow-release activating particles is 5~15 μm, and the thickness of the silica sol coating layer is 0.1~3 μm. The particle size of the slow-release activating particles is determined by the particle size of the mechanically activated blast furnace slag powder and the thickness of the silica sol coating layer, and the thickness of the silica sol coating layer is positively correlated with the mass fraction of SiO2 in the silica sol. For example, when the mass fraction of SiO2 in the silica sol is 25%, the thickness of the silica sol coating layer is about 1.2 μm.
[0046] S2. Weigh the following components by weight: 256 parts cement; 508 parts ultrafine dolomite powder; 110 parts slow-release activating granules; 183 parts water; 1095 parts river sand; 2 parts water-reducing agent; mix the water-reducing agent with water and let stand for 10-20 minutes to obtain a mixed solution.
[0047] S3. Weigh out ordinary silicate cement, ultrafine dolomite powder with a particle size of less than 3 μm and slow-release activating particles, and put them into a mixer and stir at 62±5 r / min for 1~2 minutes to obtain a mixed powder.
[0048] S4. Add 2 / 3 of the volume of the mixed solution into the mixer and stir at 62±5 r / min for 1~3 minutes to obtain a mixed slurry;
[0049] S5. The weighed river sand is added to the mixer and stirred at 62±5 r / min for 1 to 3 minutes. Then the remaining mixed solution is added and stirred at 125±10 r / min to obtain a mixed slurry.
[0050] S6. The mixed slurry is injected into a mold and cured in a curing environment with a temperature of 20±2℃ and a relative humidity of ≥95% to form a solidified material. After curing, the material is demolded and cured in the same curing environment for 1 to 28 days to obtain a high-strength cement-based material.
[0051] Example 2
[0052] This embodiment provides a low-heat, high-strength cement-based material and its preparation method. The preparation process is similar to that of Embodiment 1, except that the weight components are: 369 parts cement; 254 parts ultrafine dolomite powder; 41 parts slow-release activating particles; 205 parts water; 1232 parts river sand; and 1 part water-reducing agent.
[0053] Example 3
[0054] This embodiment provides a low-heat, high-strength cement-based material and its preparation method. The preparation process is similar to that of Embodiment 1, except that the weight components are: 328 parts cement; 254 parts ultrafine dolomite powder; 82 parts slow-release activating particles; 205 parts water; 1232 parts river sand; and 1 part water-reducing agent.
[0055] Example 4
[0056] This embodiment provides a low-heat, high-strength cement-based material and its preparation method. The preparation process is similar to that of Embodiment 1, except that the weight components are: 428 parts cement; 620 parts ultrafine dolomite powder; 48 parts slow-release activating particles; 238 parts water; 1429 parts river sand; and 2 parts water-reducing agent.
[0057] Example 5
[0058] This embodiment provides a low-heat, high-strength cement-based material and its preparation method. The preparation process is similar to that of Embodiment 1, except that the process for preparing the slow-release activated particles involves first using a ball mill or vibratory mill to mechanically activate the blast furnace slag powder. The specific surface area of the mechanically activated blast furnace slag powder is controlled to be between 850 and 900 m². 2 / kg; then, the mechanically activated blast furnace slag powder is added to a silica sol dispersion and uniformly dispersed for coating treatment, so that the surface of the blast furnace slag powder is coated with a continuous silicon-oxygen network structure. The mass fraction of SiO2 in the silica sol is 15%; finally, the coated blast furnace slag powder is heat-treated at 120 ℃ for 2 h to improve the structural stability of the silica sol coating layer; the thickness of the silica sol coating layer is about 0.3 μm, and the particle size of the prepared slow-release activating particles is 3~5 μm.
[0059] Comparative Example 1
[0060] This comparative example provides a cement-based material and its preparation method. The preparation process is similar to that of Example 1, except that it does not contain ultrafine dolomite powder and slow-release activating particles. The other components by weight are: 456 parts of ordinary silicate cement; 1369 parts of river sand; 229 parts of water; and 1 part of water-reducing agent.
[0061] Comparative Example 2
[0062] This comparative example provides a cement-based material and its preparation method. The preparation process is similar to that of Example 1, except that it does not contain slow-release activating particles. The other components by weight are: 366 parts of ordinary silicate cement; 508 parts of ultrafine dolomite powder; 1095 parts of river sand; 183 parts of water; and 2 parts of water-reducing agent.
[0063] Comparative Example 3
[0064] This comparative example provides a cement-based material and its preparation method. The preparation process is similar to that of Example 1, except that it does not contain ultrafine dolomite powder. The other components by weight are: 319 parts of ordinary silicate cement; 137 parts of slow-release activating particles; 1369 parts of river sand; 229 parts of water; and 1 part of water-reducing agent.
[0065] It should be noted that, since some components are missing in the comparative examples, the weight ratios of other components have been adaptively adjusted based on the same water-to-binder ratio and mortar ratio per unit volume, so that the performance of the examples and the comparative examples is comparable under the same design conditions.
[0066] Comparative Example 4
[0067] This comparative example provides a cement-based material and its preparation method. The preparation process is similar to that of Example 1, except that the slow-release activating particles are not coated with silica sol and subjected to subsequent heat treatment, and are blast furnace slag powder with a particle size of 5~15 μm.
[0068] Comparative Example 5
[0069] This comparative example provides a cement-based material and its preparation method. The preparation process is similar to that of Example 1, except that the dolomite powder has a particle size of 3~10 μm.
[0070] Comparative Example 6
[0071] This comparative example provides a cement-based material and its preparation method. The preparation process is similar to that of Example 1, except that the particle size of the slow-release activating particles is 15~50 μm.
[0072] Table 1. Reduction in cumulative heat of hydration and peak temperature rise in the examples and comparative examples.
[0073]
[0074] Table 2 Mechanical property parameters of the products obtained in the examples and comparative examples
[0075]
[0076] Referring to Tables 1 and 2, compared with Comparative Example 1 which did not contain ultrafine dolomite powder and slow-release activating particles, the cement-based materials prepared in the embodiments of the present invention (with similar results in Examples 1-4) all exhibited excellent process heat release performance and mechanical properties. The cumulative heat of hydration in Example 1 was reduced by 47.48%, and the peak temperature rise decreased from 58.4 ℃ to 31.7 ℃; the cumulative heat of hydration in Example 5 was reduced by 40.4%, and the peak temperature rise decreased from 58.4 ℃ to 41.8 ℃; at the same time, the compressive strength and flexural strength of Example 1 at 1 day, 7 days, and 28 days were all improved, indicating that the present invention can take into account the development of the early and late mechanical properties of the material while reducing the heat of hydration release level.
[0077] See Figure 1 The cumulative heat release curves of the system of this invention are generally lower than those of Comparative Examples 1-3, and the cumulative heat release curves of Comparative Examples 2 and 3 are generally lower than those of Comparative Example 1. This indicates that using nucleating inert powder or slow-release activating particles alone can reduce the cumulative heat release during cement hydration to a certain extent, but the performance is not as good as the example in which nucleating inert powder and slow-release activating particles are added together. This shows that through the synergistic effect of particle components with different functional properties, the total heat release of the system can be effectively reduced, thereby reducing the accumulation of heat of hydration from the source. See also Figure 2The exothermic rate of the system in this invention is significantly lower than that of Comparative Example 1. Compared to Comparative Example 1, the duration of the exothermic process in the embodiment is prolonged, indicating that the system has achieved a transformation from the traditional single-peak concentrated exothermic process to multi-stage distributed exothermic process, thereby reducing the phenomenon of concentrated heat release in the early age and helping to reduce internal temperature rise and temperature gradient. Furthermore, the exothermic rate of the embodiment is significantly lower than that of Comparative Examples 2 and 3, indicating that the synergistic effect of nucleating inert powder and slow-release activating particles has a significant advantage, improving the phenomenon of concentrated heat release in the early age of cement. Although the flexural strength and compressive strength of Comparative Example 2 are higher than those of the embodiment, its cumulative heat of hydration and peak temperature rise are much higher than those of the embodiment, and it releases more heat in the early stage, which will lead to some potential cracks and have a significant impact on the long-term durability of cement-based materials.
[0078] See Figure 3 The cumulative exothermic curve of the system of this invention is generally lower than that of Comparative Example 4, indicating that the synergistic effect of the nucleating inert powder and the slag particles without silica sol coating is not as good as that of Example 1. This shows that the slag particles of this invention can effectively reduce the cumulative exothermic heat after being coated with silica sol. See also Figure 4 The exothermic rate of the system of the present invention is significantly lower than that of Comparative Example 4. This indicates that the improvement effect of the slow-release activating particles coated with silica sol is better than that of the uncoated slag particles. The main reason is that the slow-release activating particles after coating exhibit inert characteristics in the early stage and do not undergo chemical reaction. Therefore, the synergistic effect of nucleating inert powder and slow-release activating particles is better in the examples.
[0079] See Figure 5 The cumulative heat release curve of Example 1 of this invention is generally lower than that of Example 5, but slightly higher than that of Comparative Examples 5 and 6. This indicates that the early nucleating powder or slow-release activating particles with larger particle sizes have a better effect on reducing heat release than the examples. However, analysis of the compressive strength data in Table 2 shows that the compressive strength of Comparative Examples 5 and 6 is much lower than that of Example 1, and even lower than that of Comparative Example 1. This indicates that although Comparative Examples 5 and 6 can effectively reduce the cumulative heat release, they significantly reduce the mechanical properties. This improvement effect is similar to that of existing invention patents. However, the system of this invention not only takes into account the improvement of mechanical properties, but also significantly reduces the cumulative heat release. The synergistic effect of nucleating inert powder with a particle size of less than 3 μm and slow-release activating particles with a particle size of 5~15 μm can present the optimal performance and effect.
[0080] See Figure 6 The exothermic rate of the system of the present invention is significantly lower than that of comparative examples 5 and 6. This indicates that the synergistic effect of nucleating inert powder with a particle size of less than 3 μm and slow-release activating particles with a particle size of 5~15 μm in Example 1 is better than that of other particle types, and can demonstrate the best improvement effect.
[0081] The experimental results show that this invention, by constructing a synergistic regulatory system composed of nucleating inert powders and slow-release activating particles, achieves distributed regulation of the cement hydration process over time, transforming the heat of hydration release process from concentrated release to phased release. Compared with existing chemical regulation methods that rely on retarders or heat of hydration inhibitors, this invention eliminates the need for complex admixture systems, avoiding compatibility issues between admixtures and different cement systems. While significantly reducing cumulative heat release, peak temperature rise, and temperature stress, it maintains or even improves the early and later mechanical properties of the material. The functional components used in this invention are mainly derived from conventional engineering materials and industrial solid waste resources, exhibiting good economic efficiency, environmental friendliness, and engineering applicability. It can be widely applied in engineering fields with high requirements for temperature control and crack prevention, such as large-volume concrete, bridge engineering, hydraulic structures, nuclear power foundations, and prefabricated buildings.
[0082] In summary, this invention provides a low-heat, high-strength cement-based material and its preparation method based on time-sequential regulation of hydration heat. By controlling the temporal characteristics of different functional particles participating in the hydration reaction, the heat of hydration release process is redistributed over time, solving the problem that traditional low-heat hydration technologies struggle to balance temperature control and mechanical properties. This invention not only effectively reduces early-age temperature rise peaks and the resulting temperature stresses but also promotes the continuous development of material strength, improving the long-term service performance and durability of structures, demonstrating significant engineering application value and promising prospects for widespread adoption.
[0083] Those skilled in the art should understand that variations can be implemented by combining existing technology with the above embodiments, which will not be elaborated here. Such variations do not affect the essence of the present invention, and will not be elaborated here either.
[0084] The preferred embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above. Systems and structures not described in detail should be understood as being implemented in a conventional manner in the art. Any person skilled in the art can make many possible variations and modifications to the technical solutions of the present invention using the methods and techniques disclosed above, or modify them into equivalent embodiments with equivalent changes, without departing from the scope of the present invention. This does not affect the essential content of the present invention. Therefore, any simple modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the present invention are still within the scope of protection of the present invention.
Claims
1. A low-heat, high-strength cement-based material based on time-division controlled heat of hydration, characterized in that: The composition includes the following components by weight: 256-428 parts cement; 254-620 parts nucleating inert powder; 41-110 parts slow-release activating granules; 183-238 parts water; 1095-1429 parts river sand; and 1-2 parts water-reducing agent. The nucleating inert powder provides nucleation sites during the early stages of cement hydration and has a particle size of less than 3 μm. The slow-release activating particles have a core-shell structure with a particle size of 3-15 μm, including an inner layer of mineral particles and an outer layer of silica sol coating with a thickness of 0.1-3 μm. The mineral particles include one or more of granulated blast furnace slag powder, fly ash, and metakaolin.
2. The low-heat, high-strength cement-based material according to claim 1, characterized in that, The cement is ordinary Portland cement.
3. The low-heat, high-strength cement-based material according to claim 1, characterized in that, The nucleating inert powder is one or more of dolomite powder, limestone powder, basalt powder, and quartz powder.
4. The low-heat, high-strength cement-based material according to claim 1, characterized in that, The sustained-release activating particles have a particle size of 5~15 μm.
5. A method for preparing a low-heat, high-strength cement-based material, characterized in that, The preparation of the low-heat, high-strength cement-based material as described in any one of claims 1 to 4 comprises: S1. Preparation of sustained-release activating particles: First, the mineral material is subjected to mechanical activation treatment by grinding. The specific surface area of the mechanically activated mineral particles is controlled at 450~900 m². 2 / kg; then the mechanically activated mineral particles are added to a silica sol dispersion for coating treatment, wherein the mass fraction of SiO2 in the silica sol is 10%~40%; finally, the mineral particles with a continuous silicon-oxygen network structure on the surface are heat-treated at 80~200 ℃ to improve the structural stability of the silica sol coating layer; the particle size of the prepared slow-release activated particles is 3~15 μm, wherein the thickness of the coating layer is 0.1~3 μm; S2. Weigh the water-reducing agent according to the ratio, mix it with water, and let it stand to obtain a mixed solution; S3. The cement, nucleating inert powder with a particle size of less than 3 μm, and slow-release activating particles weighed according to the proportion are put into the mixer and stirred evenly to obtain a mixed powder. S4. Add 2 / 3 of the volume of the mixed solution into the mixer and continue to stir until homogeneous to obtain a mixed slurry; S5. The river sand weighed according to the proportion is added to the mixer and stirred. Then the remaining mixed solution is added and stirred to obtain a mixed slurry. S6. The mixed slurry is injected into a mold for curing to form a solidified material; after curing, the material is demolded and cured for 1 to 28 days under the same curing environment to obtain a high-strength cement-based material.
6. The preparation method according to claim 5, characterized in that, Before adding the remaining mixed solution, the mixer is stirred at a speed of 62±5 r / min. After adding the remaining mixed solution, the mixer is stirred at a speed of 125±10 r / min.
7. The preparation method according to claim 5, characterized in that, In steps S4 to S6, the peak temperature rise of the hydration reaction does not exceed 31.7 °C.
8. The low-heat, high-strength cement-based material prepared by the preparation method according to any one of claims 5 to 7.
9. The low-heat, high-strength cement-based material according to claim 8, characterized in that, The flexural strength of the low-heat, high-strength cement-based material is not less than 9.6 MPa, and the compressive strength is not less than 57.9 MPa.
Citation Information
Patent Citations
Cement hydration rate regulating material as well as preparation method and application of cement hydration rate regulating material
CN104609767A
Material for regulating hydration rates of different minerals in cement, and preparation method thereof
CN109293273A
Low-heat cementing material and preparation method thereof
CN116282977A
Anti-crack expansive concrete and preparation method thereof
CN120943591A
Concrete hydration heat temperature inhibitor as well as preparation method and application thereof
CN121377600A